THEME OF UKRAINE IN ARTISTIC AND JOURNALISTIC DISCOURSE OF VASYL STEFANYK - Hnatiuk, Mykhailo (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The author of the article analyzes V. Stefanyk's short stories, in which the author comprehends the formation of the national consciousness of Ukrainians after the failure of the liberation struggles of 1918-1920.Patriotic theme that at the turn of the ХІХ-ХХ centuries found artistic embodiment in the image of the offended peasantry, in the second period of the writer's work (1916-1936) was realized in stories depicting the formation of a new generation of nationally conscious Ukrainians who came out of this peasantry. The author of the study analyzes the short stories "Maria", "Sons", involving in the analysis the journalism and correspondence of the writer. This suggests that the works of V. Stefanyk of this period became one of the brightest patriotic examples of Ukrainian literature of the first half of the twentieth century.